Alpian1*, Kilinton Sihombing2 , Herwin Joni1 , Mahdi Santoso1 , Grace Sisca1 , Wahyu Supriyati1: KARAKTERISTIK ARANG AKTIF DARI SERBUK LIMBAH KAYU UNTUK MENINGKATKAN KUALITAS AIR (Characteristics of Active Charcoal from Powder Wooden Waste which is Applicable for Improving Water Quality) - JHT, Admin (Jurnal Hutan Tropika, 2021)
The waste of wood processing industry such as the plywood, sawmill and woodworkingindustries give waste as form of end pieces, slash, peeling residue, scrap and sawdust.The wood waste is not utilized by the furniture industry. The solution of this problem isto process these wood waste into activated charcoal. Activated charcoal can be madefrom any material containing carbon, both organic and inorganic, provided that thematerial is porous.The first,the waste wood of Ulin, Benuas, and Agathis used asmaterials in this study were carbonized and then made into activated charcoal. Thequality test of activated charcoal were yield, moisture content, ash, volatile matter, fixedcarbon, absorption of benzene, absorption of iodine and absorption of methylene blue.Overall, not all research treatments on the quality of activated charcoal fulfill to SNI 06-3730-1995. The quality of Agathis wood activated charcoal has the best quality (520,83mg/g) from all treatments by the highest score of iodine absorption (Kimia Farma (KF)standard requires >426.5 mg/g). Based on the standar of drinking water quality No.416/Menkes/Per/IX/1990, activated charcoal of agathis wood can improve the quality ofbore well water except for turbidity.Keywords: Activated charcoal, ulin, benuas, agathis, bore well water